Synthesis and Biological Evaluation of N-Heterocyclic Substituted Fluoro-Benzothiazole Sulphonamido Analogs as a Potential Therapeutic Agents - T, Sri Ranga.; Chaubey, Neelesh (Journal of Biomedical and Pharmaceutical Research, 2022)
The present investigation is aimed to synthesize fluorobenzothiazole comprising sulphonamido pyrazole analogs starting from fluoro-chloroaniline to get 2-amino-6-fluoro-7-chloro (1,3) benzothiazole (I), this was treated with anilino-s-methyl ethylene cyanoacetamide in the presence of ethanol to get desired molecules. The synthesized targeted molecules are characterized, docked and screened for their invitro antidiabetic properties. Keywords: Fluorobenzothiazole, Docking, antidiabetic